2017
DOI: 10.2141/jpsa.0160070
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Value of Mulberry Leaf Meal and its Effect on the Performance of 35-70-Day-Old Geese

Abstract: Availability of feed crops for animal production is decreasing, creating a need to identify alternative food sources. With their high protein content, mulberry leaves are a likely candidate for feed supplementation and have been trialed on pigs and chickens, but little is known about their effect as a feed supplement on geese. Here, we determine the nutritive value of mulberry leaf meal (MLM), measure the digestibility of energy and amino acid of MLM in male Sichuan white geese, and evaluate the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 13 publications
4
27
0
Order By: Relevance
“…Henceforth, we suggest that the AME values reported in many studies calculated with such flawed assumptions need to be recalculated (Adeola et al, 2010 , 2018 ; Bolarinwa and Adeola, 2012 ; Adebiyi and Olukosi, 2015 ; Pekel et al, 2015 ; Olukosi et al, 2017 ). Furthermore, Wang et al ( 2017a , b ) calculated AME of dry citrus pulp and mulberry leaf meal by using energy metabolizability coefficient of test diets (C td , calculated in their equation as [GEdiet − GEexcreta]/GEdiet) rather than that of test ingredients (C ti ). Apparently, dry citrus pulp and mulberry leaf meal have lower metabolizability than the test diets; thus, their energy content can be overestimated significantly.…”
Section: Flaws In Me Bioassaymentioning
confidence: 99%
“…Henceforth, we suggest that the AME values reported in many studies calculated with such flawed assumptions need to be recalculated (Adeola et al, 2010 , 2018 ; Bolarinwa and Adeola, 2012 ; Adebiyi and Olukosi, 2015 ; Pekel et al, 2015 ; Olukosi et al, 2017 ). Furthermore, Wang et al ( 2017a , b ) calculated AME of dry citrus pulp and mulberry leaf meal by using energy metabolizability coefficient of test diets (C td , calculated in their equation as [GEdiet − GEexcreta]/GEdiet) rather than that of test ingredients (C ti ). Apparently, dry citrus pulp and mulberry leaf meal have lower metabolizability than the test diets; thus, their energy content can be overestimated significantly.…”
Section: Flaws In Me Bioassaymentioning
confidence: 99%
“…(2010) reported that, with an increase of mulberry flour in diet, a linear decrease in the body-weight of broilers was observed, together with a quadratic effect in feed intake and conversion. In the study by Wang et al. (2016) , geese fed mulberry leaf meal exhibited low weight gains, elevated feed consumption, and increased feed to gain ratio compared with geese without mulberry in their diet.…”
Section: Discussionmentioning
confidence: 98%
“…Mulberry leaves do not significantly increase the production of poultry meat and eggs, nor do they accelerate the growth rate of poultry ( Saenthaweesuk, 2009 ; Olteanu et al., 2015 ). Researchers have suggested that diets containing ≥4% mulberry leaf powder would inhibit feed intake and body-weight gain of poultry ( ItzáOrtiz et al., 2010 ; Wang et al., 2016 ). However, it is not known why nutrient-rich mulberry leaves are unsuitable for poultry.…”
Section: Introductionmentioning
confidence: 99%
“…Total body weight gain was more in supplemented treatment, this increase in body weight may be because of its properties like increase protein utilization, rich protein source and have immunomodulatory properties (Khan et al, 2005). Additionally the positive effect on LBW, BWG, FCR due to feeding mulberry supplemented diet a good source of protein for animals (Wang et al, 2017). But improvement of FCR might be stimulating digestive enzymes followed by better digestion and utilization of feed.…”
Section: Dietary Treatmentsmentioning
confidence: 95%